2013
DOI: 10.7314/apjcp.2013.14.9.5421
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Gamma-oryzanol on Human Prostate Cancer Cells

Abstract: Background: To assess the antioxidant effects of gamma-oryzanol on human prostate cancer cells. Materials and Methods: Cytotoxic activity of gamma-oryzanol on human DU145 and PC3 prostate cancer cells was determined by proliferation assay using 3-(4, 5-dimethylthiazol, 2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) reagent. mRNA levels of genes involved in the intracellular antioxidant system, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX) and glutathione reductase (GSR) were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Gamma oryzanol is a mixture of phytosteryl ferulates found in rice bran. It is particularly important to note that γ-oryzanol exhibits antioxidant, anti-carcinogenesis and anti-inflammatory properties (Henderson et al, 2012;Klongpityapong et al, 2013). Here, we report for the first time that γ-oryzanol reduced MDA-MB-231 cell invasion, which corresponded with the finding that Hex and DCM fractions reduced cancer cell invasion.…”
Section: Discussionsupporting
confidence: 83%
“…Gamma oryzanol is a mixture of phytosteryl ferulates found in rice bran. It is particularly important to note that γ-oryzanol exhibits antioxidant, anti-carcinogenesis and anti-inflammatory properties (Henderson et al, 2012;Klongpityapong et al, 2013). Here, we report for the first time that γ-oryzanol reduced MDA-MB-231 cell invasion, which corresponded with the finding that Hex and DCM fractions reduced cancer cell invasion.…”
Section: Discussionsupporting
confidence: 83%
“…Compounds B2-B4 with a good scavenging activity were further investigated with human fibrosarcoma cells due to the relationship between antioxidant activity and chemoprevention previously reported (Tangjitjaroenkun et al, 2012;Klongpityapong et al, 2013). For cytotoxicity assay, IC 50 values at 1-and 4-day treatments cannot be DOI:http://dx.doi.org/10.7314/APJCP.2015.16.13.5371 Antioxidant Effects of Berberine and Phenolic Derivatives Against Human Fibrosarcoma Cells calculated because the survival cells were higher than 50%.…”
Section: Discussionmentioning
confidence: 99%
“…were electrophoretically analyzed on a 2% agarose gel, stained by 2% ethidium bromide, and photographed (Klongpityapong et al, 2013; …”
Section: Rna Extraction and Reverse Transcriptase Pcrmentioning
confidence: 99%
“…Germination is a strategy for improving cereal quality. Several studies have demonstrated anti-inflammatory and antioxidant activities of GABA, 50,51 γ-oryzanol, [52][53][54] γ-tocotrienol, 55,56 and ferulic acid 57,58 and their concentrations are elevated in germinated brown rice. Thus, the present study measured GABA, γ-tocotrienol, γ-oryzanol, ferulic acid and p-coumaric acid by HPLC and confirmed that the quantities of such compounds in cooked parboiled germinated brown rice (PGBR) was significantly greater than that in cooked brown rice (BR).…”
Section: Discussionmentioning
confidence: 99%